Made-to-Measure Mass Transit. - Jones, W.D.
This paper disccusses the ULTra project (ultra light transport) which is designed by Advanced Transport Systems. UTRA is one example of a mode of quasi-public transportation known as personal rapid transit, or PRT. According to PRT purists-including the board of the Advanced Transit Association, which advocates the use of technology to solve transportation problems-this label can be applied to transit systems that have all the following characteristics: fully automated vehicles that run on a reserved guideway; small vehicles that can, like taxis, provide exclusive use for small groups or even a single passenger; nonstop service using the most direct route avail-able; off-line way stations; and on-demand access to vehicles instead of fixed schedules. Because this will be the first true PRT system to go into passenger service, the ULTra project is a test case for whether all the claims made by PRT proponents are true. Proponents maintain that PRT can be an important complement to existing mass-transit systems such as light rail, commuter trains, and buses. PRT advocates also predict that personal rapid transit systems will entice people to drive less, reducing the congestion, energy consumption, and environmental impact from passenger car traffic
Keywords: Advanced Transport Systems; ULTra project; Energy consumption; Environmental impact; Personal rapid transit; Quasipublic transportation; Ultralight transport